The last of the mohicans: a narrative of 1757 ebook - Cooper, James Fenimore (Leatherstocking Tales, 2012)
The Last of the Mohicans is the second book in Cooper's Leatherstocking Tales pentalogy, and remains his best-known work. It is a historical novel set in the French and Indian war in New York, and centers around the massacre of surrendered Anglo-American troops. The two daughters of the British commander are kidnapped, but rescued by the last two Mohicans. The title comes from a quote by Tamanend: "I have lived to see the last warrior of the wise race of the Mohicans".